Behavior of Reactive Powder Concrete Deep Beams (Al-Mansour Journal, 2022)
This investigation includes the behavior and shear strength characteristics of reactive powder concrete (RPC) deep beams subjected to concentrated loads.Seven reinforced deep beams made with RPC were cast and tested. The test variables included the shear span to effective depth ratio, and percentage of silica fume in the concrete. The effect of these parameters on the behavior of the test beams included deflection, concrete strains, failure mode, and ultimate loads were investigated.The experimental results are compared with analytical results using the strut and tie model of ACI 318M-11 Code and found both results to be, in general, in good agreemsnt.
Keywords: Reactive Powder Concrete; Deep beams; Strut and Tie Model